PENGARUH PENGETAHUAN MANAJEMEN KAS DAN DIGITALISASI USAHA TERHADAP KEBERLANGSUNGAN USAHA UMKM SEKTOR INDUSTRI KREATIF PASCA PANDEMI COVID 19 - Khoirunnisa Firdarini; Manendha Maganitri Kundala (Jurnal Manajemen Dirgantara, 2024)
Micro, small, and medium enterprises are one of the driving sectors of the nation's economy. However, this sector has experienced a significant decrease in income during the Covid-19 pandemic due to social distancing regulations, posing a threat to their survival. This necessitates SMEs to enhance their knowledge and capability in cash management to achieve cost efficiency. Social distancing regulations also demand SMEs to adapt to technology, thus they need to digitalize their businesses, including business management and marketing. This research focuses on SMEs in the creative industry sector in Yogyakarta Special Region, specifically in the culinary, fashion, and crafts businesses, which are the three largest sectors in the region. The aim of this research is to examine the influence of cash management knowledge and business digitalization on the sustainability of SMEs post-Covid-19 pandemic. Data collection involved distributing questionnaires to 100 respondents who met purposive sampling criteria. Hypothesis testing was conducted using Structural Equation Modeling (SEM) - Partial Least Squares (PLS). Based on the testing, it was found that cash management does not influence business sustainability, while business digitalization has a significant impact on SME sustainability.